The Influence Of Employer Branding and Social Media on Generation Z’s Job Application Intentions with the Mediating role of Company Reputation - Nurus Syafaatul Laila; Ryan Basith Fasih Khan (Economic and Bussiness Faculty, Dr Soetomo University, 2024)
With the development of the era and the acceleration of globalization from various aspects, companies need to have a workforce that is able to manage and is ready to face changes that can affect the company. Generation Z is the focus of the study because they have different views on finding a job, namely prioritizing stability in work and benefits and high starting salaries (survey by the Handshake career site, 2022). The population in this study was 259 respondents with 157 samples taken using the Slovin formula. The data sources utilized include both primary and secondary data. Data collection was conducted through a questionnaire using Google Forms. Data analysis was performed using PLS SEM with the SmartPLS 4 software. The study results indicated that employer branding and social media have a positive and significant impact on company reputation. Employer branding positively and significantly influences job application intentions. Social media has a negative and insignificant effect on job application intentions. The favorable and notable influence of a company's reputation extends to job application intentions. Employer branding and social media positively and significantly affect job application intentions, with company reputation acting as a mediator.